Guanidinoacetic acid effects on ruminal fermentation, digestibility and methane production in sheep liquor: Dose-response analysis - Oscar Vicente Vazquez-Mendoza; Mona M.M.Y. Elghandour; Maria A. Mariezcurrena Berasain; Udoh A. Inyang; Akaninyene Jack; Maximilian Lackner; Abdelfattah Z.M. Salem (Journal of Agriculture and Food Research)
Guanidinoacetic acid (GAA), a precursor of creatine, is partially degraded in the rumen when unprotected. While GAA has shown promise as a feed additive, its optimal dose for ruminants remains unclear. This study investigated the dose-response effects of GAA on in vitro ruminal fermentation and greenhouse gas production in fattened sheep. Rumen inoculum from two Pelibuey sheep (30 kg ± 2 kg) fed a 50:50 forage: concentrate diet was used to test seven GAA doses: 0 (GAA0, control), 500 (GAA0.5), 1000 (GAA1), 1500 (GAA1.5), 2000 (GAA2), 2500 (GAA2.5), and 3000 (GAA3) mg/kg DM (dry matter). A completely randomized design was employed. GAA0.5 produced significantly higher total gas than GAA2. The CH4 production was similar across doses, except for GAA2.5, which was significantly higher than GAA0 and GAA0.5. GAA exhibited quadratic relationships with total gas production and linear relationships with CH4 and CO production but no significant effect on H2S. GAA linearly increased DM digestibility without significantly affecting ruminal fermentation profiles. GAA inclusion strongly influenced crude protein (CP) digestibility and degradability kinetics, with varying effects at different time points. The rate constant for degradation of the insoluble but potentially degradable CP fraction was highest with GAA1. In conclusion, GAA supplementation at GAA0.5 improved total gas production without increasing CH4 emissions, implying enhanced fermentation efficiency and improved performance. GAA's impact on CP digestibility varied with incubation time. These findings provide insights into developing optimal GAA dose/level supplementation that is effective in fattening sheep, though further in vivo studies are warranted to validate these effects and explore long-term impacts on rumen microbial populations and protein utilization.